Critical discourse analysis on the representation of the female detective character in the Borderless Fog film - Sunarsih, Sunarsih; Kurniawati, Neni (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study examines manifestations of gender inequality and power relations in the film Borderless Fog (2024), nominated for Best Picture at the Indonesian Film Festival. Employing Sara Mills' Critical Discourse Analysis (CDA), the research analyzes dialogues involving the female protagonist, Sanja Arunika, to reveal how linguistic choices reflect gender-based power relations. Using a qualitative, interpretive approach, it analyzes the film's English-subtitled script to investigate how the female detective protagonist, Sanja, is constructed in relation to dominant patriarchal discourses and gendered power relations. Selected script segments are contextualized and interpreted to uncover the implication stance on gender representation in societal norms. The findings demonstrate that male characters consistently position Sanja as an object through utterances emphasizing her physical appearance, fragility, or external affiliations, thereby diminishing her role and undermining her professional authority. While the film challenges stereotypes by portraying Sanja as competent and resilient, it simultaneously critiques the systemic patriarchal structures embedded in male-dominated professions. The discussion connects these findings to broader feminist discourse, highlighting how media representations can either perpetuate or contest gender inequality. This study contributes to the understanding of gender dynamics in Indonesian cinema, which simultaneously reproduces and subverts gender norms within institutional and cultural contexts.